P075 Muc5ac expression protects the colonic barrier in experimental colitis. (15th January 2020) - O'Connell, L; Olli, K; Rapp, C; Collins, C; McNamee, E; Jensen, O; Jedlicka, P; Allison, K; Goldberg, M; Gerich, M; Evans, C; AHERNE, C
Abstract: Background: The mucus gel layer (MGL) lining the colon is integral to exclusion of bacteria and maintaining intestinal homeostasis in health and disease. MGL defects allowing bacteria to directly contact the colonic surface are commonly observed in ulcerative colitis (UC). The major macromolecular component of the colonic MGL is the secreted gel-forming mucin, MUC2, whose expression is essential for homeostasis in health. In UC, another gel-forming mucin, MUC5AC is induced. In mice, Muc5ac is protective during intestinal helminth infection. Here, we tested the expression and functional role of MUC5AC/Muc5ac in colitis patient biopsies and murine colitis. Methods: We measured MUC5AC/Muc5ac expression in UC patient biopsies and during acute dextran sulphate sodium (DSS) colitis. We performed DSS-colitis in mice deficient in Muc5ac (Muc5ac −/− ) to model the potential functional role of Muc5ac in colitis. To assess MGL integrity, we quantified bacterial–epithelial interaction and translocation to mesenteric lymph nodes (MLNs). Antibiotic treatment was performed to directly investigate the role of colonic bacteria in our murine colitis studies. Results: Colonic MUC5AC/Muc5ac mRNA expression increased significantly in active UC and murine colitis. Muc5ac −/− mice experienced worsened injury and inflammation in DSS-colitis compared with controls. This was associated with increased bacterial–epithelial contact and translocation to the MLN. Antibiotic treatment normalised colitis severity in Muc5ac −/− mice to that of antibiotic treated controls. Conclusion: We demonstrate for the first time that MUC5AC/Muc5ac induction in acute colitis controls injury by reducing bacterial breach of the MGL. Therefore, developing strategies to induce MUC5AC expression may protect the intestinal barrier in UC.